2017
DOI: 10.4254/wjh.v9.i14.657
|View full text |Cite
|
Sign up to set email alerts
|

Image quality and diagnostic performance of free-breathing diffusion-weighted imaging for hepatocellular carcinoma

Abstract: AIMTo retrospectively evaluate the diagnostic performance of free-breathing diffusion-weighted imaging (FB-DWI) with modified imaging parameter settings for detecting hepatocellular carcinomas (HCCs).METHODSFifty-one patients at risk for HCC were scanned with both FB-DWI and respiratory-triggered DWI with the navigator echo respiratory-triggering technique (RT-DWI). Qualitatively, the sharpness of the liver contour, the image noise and the chemical shift artifacts on each DWI with b-values of 1000 s/mm2 were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Although several DW imaging sequences can be applied to evaluate the liver, the single shot spin-echo (SE) echo-planar technique is the most frequently used in combination with fat suppression. Recent studies[ 68 ] compared free breathing (FB) vs respiratory triggered (RT) DWI for detecting HCC, using a 3 T scanner, a 32-channel torso-cardiac phased-array coil, and dual-source parallel radiofrequency excitation and transmission technology. They concluded that FB-DWI provided better image quality and showed higher detectability of HCCs in patients with chronic liver disease compared to RT-DWI, without significantly reducing the SNR of the normal liver parenchyma or the lesion-to-non lesion CNR.…”
Section: Diffusion Weighted Imagingmentioning
confidence: 99%
“…Although several DW imaging sequences can be applied to evaluate the liver, the single shot spin-echo (SE) echo-planar technique is the most frequently used in combination with fat suppression. Recent studies[ 68 ] compared free breathing (FB) vs respiratory triggered (RT) DWI for detecting HCC, using a 3 T scanner, a 32-channel torso-cardiac phased-array coil, and dual-source parallel radiofrequency excitation and transmission technology. They concluded that FB-DWI provided better image quality and showed higher detectability of HCCs in patients with chronic liver disease compared to RT-DWI, without significantly reducing the SNR of the normal liver parenchyma or the lesion-to-non lesion CNR.…”
Section: Diffusion Weighted Imagingmentioning
confidence: 99%
“…Regarding the upper abdominal region, breathing is considered to be an influencing factor, but Takayama et al 35,36 could show good results by the use of free-breathing DWI compared with respiratory-triggered DWI. Consequently, both s-DWI and opt-DWI were performed under free-breathing conditions, leading to good image quality in both sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The same thing happens when the tissue has many small cells within the lesion, and HCC is known to have many small cells compared with normal hepatocytes. Therefore, the cells number in HCC is higher than the normal liver cells [15] . Thus, the diffusion of water is restricted, and this could be indicated by the low value of Apparent diffusion coefficient (ADC) [16] which is considered as post-processing of DWI sequences [15] .…”
mentioning
confidence: 92%
“…Therefore, the cells number in HCC is higher than the normal liver cells [15] . Thus, the diffusion of water is restricted, and this could be indicated by the low value of Apparent diffusion coefficient (ADC) [16] which is considered as post-processing of DWI sequences [15] . Therefore, the diffusion restriction indicates the signal intensity of a tumour which is higher compared with the surrounding parenchyma, and the b-value (expressed in seconds per millimeter square) DW MR images would be high [17] , Also, the restriction of diffusion in malignant tumours is higher than the benign lesions [18] .…”
mentioning
confidence: 92%
See 1 more Smart Citation